2022
DOI: 10.1080/14756366.2022.2058499
|View full text |Cite
|
Sign up to set email alerts
|

Natural source, bioactivity and synthesis of 3-Arylcoumarin derivatives

Abstract: 3-arylcoumarins with different pharmacological properties widely exist in a variety of natural plants. The extensive research on 3-arylcoumarins was attributed to its therapeutic and relatively easy isolation. Therefore, 3-arylcoumarins can be recognised as useful structures for the design of novel compounds with potential pharmacological interest, particularly in the fields of anti-inflammatory, anti-cancer, antioxidant, Monoamine oxidase (MAO) enzyme inhibition, etc. The current review highlights the biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…The search for natural-source compounds with pharmacological properties has resulted in the discovery of one of the many new molecules with critical applications [ 1 , 2 ]. Ethiopia stands out as a potential source of these natural chemicals because it has the highest plant biodiversity in the world and the bulk of its species are yet to be found in terms of their therapeutic potential [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The search for natural-source compounds with pharmacological properties has resulted in the discovery of one of the many new molecules with critical applications [ 1 , 2 ]. Ethiopia stands out as a potential source of these natural chemicals because it has the highest plant biodiversity in the world and the bulk of its species are yet to be found in terms of their therapeutic potential [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This condition is becoming more widespread every day, and it primarily affects the elderly. Recent studies have demonstrated that this disease can be managed by PDCs [137] …”
Section: Results From the Reviewing And Their Related Discussionmentioning
confidence: 99%
“…Non-competitive inhibition involves a molecule that binds to a location on the enzyme other than the active site, thereby altering the enzyme’s conformation and reducing its activity. Uncompetitive inhibition involves a molecule that binds to the enzyme-substrate complex, preventing the enzyme from catalysing the reaction 4 .…”
Section: Introductionmentioning
confidence: 99%